Methods of Studying the Architectural Style and Environment Formation in Creating Design-Code Rules of the City of Bukhara (Journal of Architectural Design, 2022)
The article talks about the analysis of the architectural style of the city of Bukhara, the methods of applying it in the design of small architectural forms by taking the model and using the elements of the historical architectural object in the modern design practice. Issues of urban space design and street beautification, reflecting an integrated approach to urban environment design and how small architectural forms and design solutions should be according to the "greening rules" section of the Design Code. recommendations on methods are given. Conclusions are made about the use of small architectural forms as elements of improving the urban environment, its goals and tasks